2014
DOI: 10.1126/scitranslmed.3007668
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A2 Induces Cardiac Regeneration After Myocardial Infarction Through Cytokinesis of Adult Cardiomyocytes

Abstract: Cyclin A2 (Ccna2), normally silenced after birth in the mammalian heart, can induce cardiac repair in small-animal models of myocardial infarction. We report that delivery of the Ccna2 gene to infarcted porcine hearts invokes a regenerative response. We used a catheter-based approach to occlude the left anterior descending artery in swine, which resulted in substantial myocardial infarction. A week later, we performed left lateral thoracotomy and injected adenovirus carrying complementary DNA encoding CCNA2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 36 publications
4
81
0
1
Order By: Relevance
“…Remarkable progress has been achieved on this front in the past decade by forced expression of general cell cycle regulators in adult cardiomyocytes, including cyclin A2 (Chaudhry et al, 2004;Shapiro et al, 2014;Woo et al, 2006), cyclin D1/2/3 (Hassink et al, 2008;Pasumarthi et al, 2005;Soonpaa et al, 1997) and cyclin-dependent kinase 2 (Cdk2) (Liao et al, 2001). In all cases, reactivation of the cell cycle regulator was achieved in rodent or porcine hearts using transgenic or viral approaches.…”
Section: Modulation Of Cardiomyocyte Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable progress has been achieved on this front in the past decade by forced expression of general cell cycle regulators in adult cardiomyocytes, including cyclin A2 (Chaudhry et al, 2004;Shapiro et al, 2014;Woo et al, 2006), cyclin D1/2/3 (Hassink et al, 2008;Pasumarthi et al, 2005;Soonpaa et al, 1997) and cyclin-dependent kinase 2 (Cdk2) (Liao et al, 2001). In all cases, reactivation of the cell cycle regulator was achieved in rodent or porcine hearts using transgenic or viral approaches.…”
Section: Modulation Of Cardiomyocyte Activitymentioning
confidence: 99%
“…Woo and colleagues further demonstrated that adenoviral injection of cyclin A2 into the border zone of infarcted rat hearts increased cardiomyocyte proliferation, as measured by PCNA antibody staining, as well as improved heart function (Woo et al, 2006). The study of Woo and colleagues was followed up by adenoviral injection of cyclin A2 into infarcted porcine hearts (Shapiro et al, 2014), a model physiologically closer to humans. The porcine model confirmed findings previously described for rodents, as virus-transduced hearts showed improved function, increased cardiomyocyte mitosis as assessed by Ki67 antibody staining, increased cardiomyocyte numbers and decreased fibrosis.…”
Section: Modulation Of Cardiomyocyte Activitymentioning
confidence: 99%
“…For example, cardiomyocyte cell cycle arrest and binucleation is correlated with a down-regulation of positive regulators of the cell cycle such as cyclins and CDKs and up-regulation of cyclin-dependent kinase inhibitors such as p21 and p27 (6). A role for cyclins in cardiomyocyte cell cycle arrest is demonstrated by the finding that cyclin A overexpression delays cardiomyocyte cell-cycle withdrawal and promotes cardiac regeneration after myocardial infarction through the promotion of cytokinesis of adult cardiomyocytes (7,8). Similarly, deletion of the homeobox protein Meis1 enhances proliferation of postnatal cardiomyocytes because it regulates the expression of cell cycle inhibitors such as p16 INK4A and p21 CIP1 (9).…”
mentioning
confidence: 99%
“…These investigators attempted to translate this into a more clinically relevant model by delivering cyclin A2 via adenovirus to infarcted porcine heart. Cyclin A2 overexpression postinfarct improves cardiac function, which was attributed, at least in part, to enhanced myocyte proliferation (98). A major limitation of studies analyzing the effects of constitutively active transgenes is to differentiate mechanisms that may include dedifferentiation and proliferation of adult cardiac myocytes, stimulation of cardioblasts as suggested above, enhanced proliferation (and differentiation) of endogenous cardiac progenitor cells, or that a subset of cardiac myocytes in the transgenic hearts never underwent terminal differentiation because of the persistent expression of a positive cell cycle activator.…”
Section: A Stimulating Cardiac Myocyte Proliferationmentioning
confidence: 98%